2021
DOI: 10.35328/keperawatan.v9i2.673
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Orientasi Pasien Baru Di Rsud Petala Bumi Pekanbaru Provinsi Riau

Abstract: Orientasi pasien baru merupakan proses penerimaan pasien baru serta keluarga pada saat pertama kali pasien datang (24 jam pertama) dan keadaan pasien sudah tenang. Hasil obsevasi peneliti, perawat belum melakukan pelaksanaan orientasi pasien baru sesuai dengan standar operasional prosedur yang telah diterapkan. Orientasi pasien baru bertujuan membina hubungan saling percaya dan informasi awal yang berkaitan dengan proses keperawatan pasien. Penelitian ini bertujuan untuk melihat pelaksanaan orientasi pasien ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results are consistent with another study that reported a 76.2% increase in compliance. 6 Furthermore, providing information about the use of facilities, procedures, and health workers are useful because most of the patients lack the knowledge. [12][13][14] Procedures for using facilities, such as the bell can also increase the response time of nurses in providing direct care to the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with another study that reported a 76.2% increase in compliance. 6 Furthermore, providing information about the use of facilities, procedures, and health workers are useful because most of the patients lack the knowledge. [12][13][14] Procedures for using facilities, such as the bell can also increase the response time of nurses in providing direct care to the patients.…”
Section: Resultsmentioning
confidence: 99%
“…5 Another study conducted at a hospital in Riau Province, Indonesia also stated that 21.4% of nurses did not orient the patient on how to use the bell, and more than 50% did not perform orientation about the rules, facilities, rights, and obligations. 6 Furthermore, the interviews with the head of the ward, where this study was conducted revealed that they already have a standard procedure for new patient admissions. However, the implementation is not optimal because many nurses do not follow the procedure completely.…”
Section: Introductionmentioning
confidence: 98%